The Impact of Political Annexation on Urban Primacy: A natural experiment on Mexico City testing the institutional origins of primacy - George Wilkinson; Fiona Haslam McKenzie; Julian Bolleter (Journal of Regional and City Planning, 2022)
Institutional theories of urban primacy suggest centralized urbanization can be decentralized through political reform. Despite this potential, rectifying primacy and its attendant inefficiencies attracts sporadic interest. Perhaps this is because the disruption of primacy is rarely observed, rendering the potential of decentralization a nebulous concept. Missing cities are a defining feature of primacy yet rarely figure in empirical cost-benefit analyses. To explore this dimension, we examine the history of urbanization in a large country renowned for primacy before and after it was invaded and divided into two countries. In the invaded part of the country, we observe the disruption of primacy following the transformation of political institutions, highlighting the importance of addressing institutions in the redress of urban primacy.